An analysis of man-machine interaction in instant messenger - Goh, Ong Sing; Fung, Chun Che; Depickere, Arnold; Wong, Kok Wai (Springer US, 2008)
The availability of multiple media channels through the Internet has added new dimensions of communication between people or communities who are geographically separated. In the environment of informal communication on the Internet, chat applications are popular in which a user may be represented only by a nickname or an alias. This suggests that a person may be able to communicate more freely when his or her identity is concealed. Popular chatting or instant messaging (IM) systems such as Microsoft MSN Messenger, America Online's Instant Messenger, Yahoo? Messenger, and GoogleTalk have changed the way that a user may communicate with friends, acquaintances, and business colleagues. Once limited to desktop personal computers (PCs) or laptops, popular instant messaging systems are finding their way onto handheld devices and mobile phones. This allows a user to chat from virtually anywhere. Nowadays, IM is found on almost every personal PC connected to the Internet as well as on many corporate desktops.